Tingkat Pengetahuan dan Kesadaran Berperilaku K3 Mahasiswa Teknik Sipil Universitas Internasional Batam - Ade Jaya Saputra; Marvin Tandedi (Jurnal Ilmiah Rekayasa Sipil, 2021)
Awareness in implementing Occupational Safety and Health (K3) is a factor that affects the number of work accidents. Awareness of K3 behavior as a preventive measure aims to reduce and even eliminate the risk of zero accidents. Such awareness can be started before entering the world of construction work. The purpose of this research is to find out the awareness of K3 behavior in the Civil Engineering study program of Batam International University. The method used in this research is by distributing questionnaires containing statements related to K3 behavior. Respondents to this study numbered 64 students of Civil Engineering UIB. Respondents who filled out questionnaires were divided into two parts, namely students in the first and second years as well as third- and fourth-year students. The results showed the total percentage of all respondents' results reached more than 85% for K3 knowledge and awareness of K3 behavior both students first and second years or as third- and fourth-year students. Universitas Internasional Batam as one of university that nurtures the next labour in construction field has made efforts in reducing the number of occupational accidents by incorporating occupational safety and health education in curriculum and providing training with certification. The demographics of Universitas Internasional Batam students also become one of the factors that most have worked also play a role in understanding students on the importance of Occupational Safety and Health (K3) in the world of work.